Pemantauan Kesehatan untuk Meningkatkan Kesehatan dan Kemandirian Pada Lansia di Panti Sosial Tresna Werda (PSTW) Kota Bengkulu - Rina Delfina; Esti Sorena; Sardaniah Sardaniah (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Maintaining health and improving health in the elderly is something that must be considered. With a healthy body condition will help the elderly body in defending itself against various diseases. The elderly due to age will experience a decline in various functions in all body systems. The elderly are a group that is susceptible to a disease, especially degenerative diseases. One of the efforts to maintain the health of the elderly can be done by conducting regular health checks at least every 6 months. The purpose of this service is to find out the health condition of the elderly at the Tresna Werda Social Home in Bengkulu City. The method used is counseling and health checks. The target of the activity is the elderly who have chronic diseases, totaling 20 people. The results of this service found that 10 elderly people suffered from hypertension, 5 people suffered from gout, 2 cataracts, 1 person suffered from COPD, and 1 person suffered from diabetes mellitus. The results of this health check are coordinated with the social care health officer to be followed up in further treatment and care. The importance of regular health checks on the elderly to find out the health problems they face and get immediate treatment to reduce the risk of further complications in the health of the elderly.